Comparative Analysis of Environmental Permitting in Indonesia and Malaysia: Implications for National Strategic Projects - Fathoni Fathoni; Febrian Febrian; Firman Muntaqo; Mohammad Nizar (Administrative and Environtmental Law Review, 2025)
This manuscript presents a comparative analysis of environmental permitting frameworks in Indonesia and Malaysia, specifically focusing on their application to large-scale development initiatives, particularly National Strategic Projects (PSN) . As developing economies, both nations grapple with the imperative of balancing economic growth with environmental sustainability. This study employs a comparative juridical–normative approach, drawing on statutory frameworks, secondary literature, and policy documents from Indonesia and Malaysia. Additionally, this study examines the legal and procedural aspects of environmental impact assessment [Analisis Mengenai Dampak Lingkungan (AMDAL) in Indonesia and Environmental Impact Assessment (EIA) in Malaysia], highlighting key similarities and differences in their approaches. While both countries possess established legislative frameworks for environmental protection, Indonesia’s accelerated permitting for the PSN, commonly facilitated by the Online Single Submission system, has drawn criticism for potentially compromising environmental safeguards and exacerbating social and environmental conflicts. Conversely, Malaysia relies on its more standardized EIA process for major projects, although it faces challenges in ensuring effective enforcement and public participation. The analysis demonstrates that despite distinct regulatory evolutions and implementation strategies, both nations share common struggles in mitigating the adverse environmental and social consequences of rapid development. The findings underscore the urgent need to strengthen environmental governance, enhance transparency, and promote meaningful stakeholder engagement to foster genuinely sustainable development pathways in Indonesia and Malaysia.